2011
DOI: 10.1258/ar.2010.100221
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic xanthoastrocytoma: MR imaging findings in 19 patients

Abstract: The pathological appearances of PXA are distinctive. MR imaging could display the morphologic features exactly, and has important diagnostic value for PXA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 12 publications
0
28
1
3
Order By: Relevance
“…Inner table scalloping is a feature of slow-growing superficial brain tumors of childhood, such as ganglioglioma and dysembryoplastic neuroepithelial tumor. 17 Whereas Crespo-Rodríguez et al 10 reported inner table remodeling in 3 of 6 patients with PXA younger than 12 years, in the study by Yu et al, 16 only 1 of the 19 patients (both children and adults with an age range of 8 -70 years) demonstrated calvarial remodeling.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Inner table scalloping is a feature of slow-growing superficial brain tumors of childhood, such as ganglioglioma and dysembryoplastic neuroepithelial tumor. 17 Whereas Crespo-Rodríguez et al 10 reported inner table remodeling in 3 of 6 patients with PXA younger than 12 years, in the study by Yu et al, 16 only 1 of the 19 patients (both children and adults with an age range of 8 -70 years) demonstrated calvarial remodeling.…”
Section: Discussionmentioning
confidence: 96%
“…We identified 3 studies with Ͼ15 patients where imaging findings were described in detail. 10,15,16 Crespo-Rodríguez et al 10 described preoperative MR imaging findings in 10 children (mean age ϭ 11.2 years, range ϭ 9 -14 years) in a publication of pediatric and adult PXAs. Eight of these tumors were cystic with a mural nodule; this feature was recognized with similar frequency in the adult population of the same study.…”
Section: Discussionmentioning
confidence: 99%
“…P leomorphic xanthoastrocytoma (PXA) is a rare low-grade astrocytoma (WHO II) which occurs in children and young adults 1,2,3 . They present with seizures, focal defi cits, intratumoral bleed and rarely with malignant transforma on 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Prior to its initial description, PXA was often classified among giant cell glioblastomas or mesenchymal tumors such as fibrous xanthomas or sarcomas (due to its rich reticulin network) 4 . In the following years, clinical and surgical series were reported 5 ; patients with PXA typically present as children or young adults with almost 70% under 30 years of age, and equal frequency of occurrence in both males and females 4,6 . Presenting symptoms consist primarily of seizures, often of long duration 3,4 ; followed by dizziness, headache and focal neurological deficit 6 .…”
mentioning
confidence: 99%
“…In the following years, clinical and surgical series were reported 5 ; patients with PXA typically present as children or young adults with almost 70% under 30 years of age, and equal frequency of occurrence in both males and females 4,6 . Presenting symptoms consist primarily of seizures, often of long duration 3,4 ; followed by dizziness, headache and focal neurological deficit 6 . Studies focusing on imaging aspects of PXA demonstrated that these tumors are often superficial with leptomeningeal extension and involve the temporal lobe most frequently (up to almost 50% in a large series) 4 ; other common locations include the parietal, frontal, and occipital lobes.…”
mentioning
confidence: 99%